2001
DOI: 10.1086/320926
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Broad-Line Seyfert 2 Galaxies in the C[CLC]f[/CLC]A and 12 μ[CLC]m[/CLC] Samples

Abstract: We report the results of a spectropolarimetric survey of the CfA and 12 mm samples of Seyfert 2 (S2) galaxies. Polarized (hidden) broad-line regions (HBLRs) are confirmed in a number of galaxies, and several new cases (F02581Ϫ1136, MCG Ϫ3-58-7, NGC 5995, NGC 6552, NGC 7682) are reported. The 12 mm S2 galaxy sample shows a significantly higher incidence of HBLRs (50%) than its CfA counterpart (30%), suggesting that the latter may be incomplete in hidden active galactic nuclei. Compared to the non-HBLR S2 galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
230
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(244 citation statements)
references
References 52 publications
13
230
1
Order By: Relevance
“…Collecting data from the literature, we found that the average luminosity of PBL Sy2s (L [ OIII] = 4.2 × 10 40 erg s −1 ) is still higher than that of NPBL Sy2s (L [ OIII] = 10 40 erg s −1 ). Although this does not give any indication of the intrinsic luminosity of the BLR, it implies that the bolometric luminosity of PBL Sy2s is on average greater than that of NPBL Sy2s, confirming what was found by Tran (2001) and Lumsden & Alexander (2001). We also found that in our sample NPBL Sy2s are on average slightly more absorbed (N NPBL H = 3 × 10 23 cm −2 ) than PBL Sy2s (N PBL H = 1.5 × 10 23 cm −2 ).…”
Section: Seyfert 2s With and Without Pblssupporting
confidence: 84%
See 1 more Smart Citation
“…Collecting data from the literature, we found that the average luminosity of PBL Sy2s (L [ OIII] = 4.2 × 10 40 erg s −1 ) is still higher than that of NPBL Sy2s (L [ OIII] = 10 40 erg s −1 ). Although this does not give any indication of the intrinsic luminosity of the BLR, it implies that the bolometric luminosity of PBL Sy2s is on average greater than that of NPBL Sy2s, confirming what was found by Tran (2001) and Lumsden & Alexander (2001). We also found that in our sample NPBL Sy2s are on average slightly more absorbed (N NPBL H = 3 × 10 23 cm −2 ) than PBL Sy2s (N PBL H = 1.5 × 10 23 cm −2 ).…”
Section: Seyfert 2s With and Without Pblssupporting
confidence: 84%
“…Seyfert 1s with significant absorption have been found (e.g., Fiore et al 2001, Cappi et al 2006, along with Seyfert 2s without X-ray absorption (e.g., Pappa et al 2001, Panessa & Bassani 2002. Furthermore, spectropolarimetric surveys indicate that only ∼ 30 − 50% of Seyfert 2s have polarized broad lines (PBLs), which might imply that not all of them harbor hidden BLRs (e.g., Tran 2001, 2003, Gu & Huang 2002. In the soft X-rays the photon index distribution is found to be skewed towards low values of Γ for obscured objects (Brightman & Nandra 2010), while in the hard X-rays, Seyfert 2s have been found to have harder spectra than Seyfert 1s (e.g., , Malizia et al 2003, Deluit & Courvoisier 2003, Ajello et al 2008a, Burlon et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…There could be several reasons why we did not detect NIR broad lines in the whole sample of AGN2: i) they could be "true" Seyfert 2, i.e. truly lack a BLR (Tran 2001;Elitzur & Ho 2009); ii) as the AGN emission is variable, it could be that we observed the source in a low state; iii) in clumpy torus models, the type 1-2 classification is probabilistic and depends on whether there or not there is a clump along the line of sight, and so stochastic variations in the dust distribution in any given source could be a reason for non-detection; iv) in particular for the more obscured sources it could be that the NIR did not allow us to completely penetrate the strong obscuration of the central engine. Regardless of the possible biases of the NIR detectability, it seems unlikely that the missed NIR BLR are hosted in AGN2 having significantly different M BH than the measured ones.…”
Section: Discussionmentioning
confidence: 92%
“…Many observational studies focused on either the detection of hidden Seyfert 1 nuclei or tracing the imprints of the dusty torus in Seyfert 2 galaxies. The spectropolarimetric study of some Seyfert 2 galaxies shows broad hydrogen recombination lines similar to those in Seyfert 1 galaxies in polarized and scattered light (e.g., Antonucci & Miller 1985;Moran et al 2000;Tran 2001;Lumsden et al 2001). For some Seyfert 2 nuclei, a weak detection of broad hydrogen recombination lines in the infrared was observed; these were presumably transmitted through the edge of the torus (Goodrich et al 1994;Veilleux et al 1997;Lutz et al 2002).…”
Section: Introductionmentioning
confidence: 90%
“…For example, several recent studies have indicated that not all Seyfert 2s contain a BLR (Tran 2001;Nicastro et al 2003;Laor 2003). Some statistical studies, although they have been criticized for selection bias (see x 4.3 for further discussion, and also Antonucci 2002), claimed intrinsic differences between Seyfert 1s and Seyfert 2s.…”
Section: Introductionmentioning
confidence: 99%